Indian patients with human immunodeficiency virus infection have high prevalence but mild severity of non-alcoholic fatty liver disease. Issue 12 (December 2022) - De, Arka; Duseja, Ajay; Badhala, Prayas; Taneja, Sunil; Sharma, Aman; Arora, Sunil
Abstract: Background and aims: Antiretroviral therapy (ART) has substantially decreased AIDS-related mortality. Non-AIDS related diseases like chronic liver disease are becoming more frequent in people living with HIV-AIDS (PLHA). Non-alcoholic fatty live disease (NAFLD) is a common etiology of liver disease in the general population. Our aim was to analyse the prevalence and risk factors of NAFLD in Indian PLHA. Methods: One hundred consecutive adults (age:36.89 ± 10.4 years, males:65%) with HIV infection were prospectively enrolled. Patients with significant alcohol intake, Hepatitis B or Cco-infection, other liver disease, malignancy or HIV stage IV were excluded. Hepatic steatosis was assessed using hepatobiliary ultrasoundand controlled attenuation parameter (CAP). Fibrosis was assessed non-invasively using FIB-4, NAFLD fibrosis score (NFS) and liver stiffness measurement (LSM). Metabolic and HIV-related risk factors were compared between PLHA with and without NAFLD. Results: Prevalence of NAFLD using CAP was 60%. Among patients with NAFLD, 27 (45%) were lean. Majority had mild-moderate steatosis. Advanced fibrosis was present in 1 (1.67%) and 4 (6.67%) patients using NFS and LSM and none using FIB-4. PLHA with NAFLD were more likely to be overweight or obese (OR = 4.21, p = 0.002) with a higher proportion of abdominal obesity (OR:25.26, p = 0.001). Other metabolic comorbidities, duration of HIV infection, duration and type of ART, CD4-count or HIV-stagewere not significantly different among PLHA with or without NAFLD. Conclusion: Prevalence of NAFLD among Indian PLHA is high although most have mild disease. Almost half of these patients are lean. HIV-related factors do not impact the risk of NAFLD. Highlights: More than half of Indian PLHA have underlying NAFLD although most have mild disease. Although PLHA with underlying NAFLD are more likely to be obese than those without NAFLD, 45% of PLHA with NAFLD are lean. HIV-related factors including duration of HIV, ART regimen, CD4-count and HIV-stage do not impact the risk of NAFLD.